Modern methods of choroid imaging - Wasiluk, Ewa; Obuchowska, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
The choroid is one of the most vascularized tissues in the body, responsible for over 70% of the blood flow in the eye. Choroid status seems to be a decisive factor in the pathogenesis of diseases such as age-related macular degeneration, central serous retinopathy, degenerative myopia, retinal vasculitis and some neoplastic diseases. However, traditional imaging methods, including indocyanine green angiography, ultrasound and optical coherence tomography (OCT), do not allow for the exact visualization of its structure. Until recently, the knowledge about choroid morphology was based mainly on post-mortem examinations. Only the application of novel modifications to the OCT technique, including enhanced depth imaging OCT (EDI-OCT), swept source OCT (SS-OCT) and OCT angiography, enabled its better visualization and examination. The increasing availability of these technologies enables fast, repeatable and non-invasive measurements of choroid thickness in everyday clinical practice. The correlation between new anatomical discoveries and functional results may make it possible to broaden the knowledge about pathogenesis of numerous eye diseases and even define new disease units.